Itty Bitty Betty Blob - Lombardo, Constance (Hippo Park, 2024)
On monster picture day, Itty Bitty Betty Blob, who prefers dancing, rainbows and cute furry creatures instead of scaring, practices being monstery on her way to school until she makes a discovery and new friends with ideas that just feel right.